2009
DOI: 10.1007/s10620-009-0721-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Retinopathy in Chronic Hepatitis C Patients Treated with Peginterferon and Ribavirin

Abstract: The purpose of this study is to evaluate the incidence and outcome of retinopathy in chronic hepatitis C patients treated with peginterferon and ribavirin. A total of 74 hepatitis C patients with baseline eye exams and eye exams during therapy were included. Retinopathy was defined as development of cotton wool spots and/or intra-retinal hemorrhage. Demographics, hepatitis C viral characteristics, treatment and laboratory data, and eye exam findings were compared in groups with and without retinopathy. Retinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
1
18
2
Order By: Relevance
“…Their study, which included a number of patients with hypertension and diabetes, 12 and 16 respectively, found that both predicted the development of interferon-associated retinopathy using logistic regression analysis. By contrast, Mehta et al [31] found higher rates of interferon-associated retinopathy in patients with hypertension and diabetes, but the differences were not statistically significant. Their study had sufficient numbers of patients with these conditions -13 patients with diabetes mellitus and 31 with hypertension -however, ophthalmological follow up was poor with less than 70% of patients receiving an eye exam within 12 weeks of starting standard of care therapy.…”
Section: Are There Any Groups That Are At Greater Risk For Developingmentioning
confidence: 84%
See 4 more Smart Citations
“…Their study, which included a number of patients with hypertension and diabetes, 12 and 16 respectively, found that both predicted the development of interferon-associated retinopathy using logistic regression analysis. By contrast, Mehta et al [31] found higher rates of interferon-associated retinopathy in patients with hypertension and diabetes, but the differences were not statistically significant. Their study had sufficient numbers of patients with these conditions -13 patients with diabetes mellitus and 31 with hypertension -however, ophthalmological follow up was poor with less than 70% of patients receiving an eye exam within 12 weeks of starting standard of care therapy.…”
Section: Are There Any Groups That Are At Greater Risk For Developingmentioning
confidence: 84%
“…Atypical adverse events: unilateral CRVO in 1 patient with a background of DM resulting in irreversible vision loss. Mehta et al [31] 18 of 64 (28%) 3 United States Baseline, 3 and 6 mo IAR: no reduced VA in eyes that developed IAR. 1 of 88 ceased treatment for asymptomatic IAR.…”
Section: How Common Is Interferon-associated Retinopathy?mentioning
confidence: 99%
See 3 more Smart Citations